PENGARUH TAKARAN PUPUK KANDANG DAN URIN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L) PADA TIGA VARIETAS - Muslih, Muslih; Jaenudin , Amran; Faqih, Achmad (Agroswagati : Jurnal Agronomi, 2021)
This experiment aims to determine the effect of cow manure and cow urine fertilizer rates on the growth and yield of shallots (Allium ascalonicum L) in three varieties. The experiment was conducted in Mekarjaya Village, Gantar District, Indramayu Regency, West Java. The research was carried out from March to June 2020. The location is situated at an elevation of 493 meters above sea level (masl), with soil types classified as latosol and regosol associations, and a C-type rainfall (moderately wet). The experimental method employed was a randomized block design (RBD) with a factorial pattern, consisting of three factors repeated three times. The first factor was cattle manure and cattle urine, consisting of three levels: 10 tons/ha, 15 tons/ha, and 20 tons/ha of cattle manure. The second factor was cattle urine, consisting of three levels: 0 cc/L, 30 cc/L, and 60 cc/L. The third factor is the variety, which consists of three levels: the Sanren variety, the Lokanata variety, and the Tuk-Tuk variety. The main observation data were analyzed using linear model statistical tests, analysis of variance, and Scott-Knot cluster post-hoc tests. The experimental results show: (1) The combination of cow manure and cow urine treatments had a significant effect on fresh tuber weight per plot and dry tuber weight per clump. However, it did not have a significant effect on plant height, number of leaves per clump, wet weight growth rate, tuber diameter, fresh weight per clump, and dry weight per plot. (2) The combination of 10 tons/ha of cow manure and 0 cc/L of cow urine on the Sanren variety achieved the highest dry tuber weight per plot, which was 3.14 kg/ha or equivalent to 14.65 tons/ha, but it was not significantly different from the other treatments.